The Cage Case. Arts and Social Neuroscience - Alfonso, Amendola; Camargo Molano, Jessica (Frontiers in Sociology, 2021)
A great story told by a musician is the basis of the best stage experimentation of the second half of the 20th century. The musician is John Cage, whose work synthesizes the entire system of arts within the extraordinary world of the avant-garde. This great story begins with the experimental artistic activities which were developed in the 1920s, consolidated in the thirties and continued through the post-war period up to the dawn of the fifties. Apart from the socio-historical cross-section Cage’s experimentation provides, it is also a pretext for reflecting on the artist’s work as well as the relationship between neuroscience and art. Important contributions to this topic come from the neuro-scientific-social research on new expressions “of creativity, imagination, genius” (Pecchinenda, 2018). This study is based on the assumption that Cage was the forerunner of neuronal experimentation that would be central to the experiments and research of many other artists. The theoretical reference model can be found in the research of the neuroscientist Kandel et al, whose work was the starting point for this investigation. Kandel grasps the definitive break between scientific logic and humanistic sensitivity in the methodological reductionism practiced by neuroscience and in the experiments of contemporary creativity. According to Kandel, both neuroscience and artistic experimentation have similar objectives and problems, and in some respects seem to develop similar methodological practices. Kandel identifies the use of memory, synthesis and knowledge of the world in authors such as Mondrian, de Kooning, Pollock, Rothko, Louis, Warhol as well as the New York school of which Cage was an important member. The relationship between art and neuroscience is synthetized in the avant-garde action of Cage and in all the artists who launched continuous attacks against traditional forms. The transition from figurative art to abstraction is “comparable” to the reductionist process that is used in the scientific field to explain complexity and phenomenology. The prolegomena of this discourse are anticipated by a previous work written by Kandel in 2012 and can also be found in other studies on the relationship between neuroscience and art, in particular in the reflections of the neurobiologist and father of neuroaesthetics, Semir Zeki. Zeki analyzed artists work as a practice perfectly comparable to the research carried out by neuroscientists. Cage, the focus of this investigation, carried out a sound-stage-vision experimentation affecting theatre, media and art which can be examined from at least two different perspectives. The first concerns the definitive subversion of “innate rules of perception” (Kandel) and the second deals with the relationship between art and neuroscience.